2012
DOI: 10.1590/s1983-14472012000200026
|View full text |Cite
|
Sign up to set email alerts
|

Educação do paciente sobre regime terapêutico medicamentoso no processo de alta hospitalar: uma revisão integrativa

Abstract: Adequate patient education about drug treatment regimen at discharge contributes to the continuity of home care. Integrative review aimed to analyze and synthesize the scientific literature about patient education on medication regimen in the hospital discharge process. We consulted the databases Medical Literature Analysis and Retrieval System on-line (MEDLINE) and Latin-American and Caribbean Center on Health Sciences Information (LILACS), and selected 24 articles published between 2005 and 2010. Inter-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
1
1
0
7
Order By: Relevance
“…Similar experiences were found in the literature review [9][10][11][12][13][14][15][16][17][18][19] and reinforced the importance and convenience in developing and updating these discharge plans instruments and corroborating their effectiveness and positive repercussion in the recovery of the health of individuals, who reiterate the protagonist position of these subjects in caring for their health.…”
Section: Resultssupporting
confidence: 73%
“…Similar experiences were found in the literature review [9][10][11][12][13][14][15][16][17][18][19] and reinforced the importance and convenience in developing and updating these discharge plans instruments and corroborating their effectiveness and positive repercussion in the recovery of the health of individuals, who reiterate the protagonist position of these subjects in caring for their health.…”
Section: Resultssupporting
confidence: 73%
“…It concluded that the intentional non-adherence can be due to complex regimes (15) , the large number of medicines that the elderly have to take, among other factors, namely cognitive deficit, difficulty in opening the distributors/ packaging of medication and memory problems. Other international Studies (16)(17)(18) concluded that, in order to avoid forgetfulness, which increases non-adherence to treatment, the health care professional could use reminders such as voice mail and telephone counseling.…”
Section: Discussionmentioning
confidence: 99%
“…Ressalta-se ainda que é um processo que deve ser iniciado já na admissão do usuário no serviço de saúde e desenvolvido durante todo o período da internação. E complementam que a existência de um plano de alta padronizado na instituição aumenta a eficácia e qualidade do cuidado prestado (Suzuki, Carmona & Lima, 2011), (Miasso & Cassiani, 2003), (Teixeira, Rodrigues & Machado, 2012), (Paiva & Valadares, 2013), (Reis et al, 2013).…”
Section: Discussionunclassified